2014
DOI: 10.1111/1346-8138.12725
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression analysis of miRNA in peripheral blood mononuclear cells of patients with non‐segmental vitiligo

Abstract: Vitiligo is a common depigmentary skin disease that may follow a pattern of multifactorial inheritance. The essential factors of its immunopathogenesis is thought to be the selective destruction of melanocytes. As a new class of microregulators of gene expression, miRNA have been reported to play vital roles in autoimmune diseases, metabolic diseases and cancer. This study sought to characterize the different miRNA expression pattern in the peripheral blood mononuclear cells (PBMC) of patients with non-segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Deregulation of miR224-3p has been reported in plasma from CRC patients [ 50 ] and peripheral blood mononuclear cells from patients with non-segmental vitiligo [ 51 ]. However, besides autophagy, the function of miR224-3p in cancer is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miR224-3p has been reported in plasma from CRC patients [ 50 ] and peripheral blood mononuclear cells from patients with non-segmental vitiligo [ 51 ]. However, besides autophagy, the function of miR224-3p in cancer is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated miRNA expression is associated with the pathogenesis of various inflammatory skin disorders such as psoriasis, atopic dermatitis, and allergic contact dermatitis (Sonkoly E et al , 2008), and there is some evidence implicating miRNAs in vitiligo. Gene expression microarray studies have revealed aberrant miRNA expression in the skin and serum of patients with vitiligo (Mansuri et al , 2014, Shi et al , 2014, Shi et al , 2013), with upregulation of miR-224-3p, miR-4712-3p, and miR-3940-5p in peripheral blood mononuclear cells (Wang et al , 2015), miR-25 upregulated in serum (Shi et al , 2016) and miR-99b, miR-125-b, miR-155, and miR-199a-3p upregulated in the skin (Šahmatova et al , 2016) of vitiligo patients. Little is known, however, about the exact role of miRNAs, their targets, and their mechanism of action in the pathophysiology of vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al examined the miRNA response in peripheral blood mononuclear cells (PBMCs) from patients with vitiligo with and without thymosin-α-1 treatment. 23 Four miRNAs showed altered expression profiles in PBMCs from non-segmented vitiligo patients, which demonstrated an inverted expression pattern post thymosin-α-1 treatment: miR-224-3p, miR-2682-3p, miR-3940-5p, and miR-4712-3p. Interestingly, miR-224-3p and miR-4712-3p have demonstrated oncogenic potential, 24,25 while miR-3940-5p has been reported to act as a tumor suppressor.…”
Section: Micro Rna Profiles Of Skin Conditionsmentioning
confidence: 94%